Analisis Kelayakan Usaha Gula Aren Di Kecamatan Marancar Kabupaten Tapanuli Selatan - Sri Wahyuni Hutagalung; Fastabiqul Khairad; Elviati Elviati (Mahesa Research Institute, 2024)
Business feasibility is a calculation to consider whether the palm sugar business will provide greater profits compared to the costs that will be incurred. The aim of this research is to determine the feasibility of the palm sugar business in Marancar District. The research population was 120 people, with the sampling method using the Slovin formula so that the sample in this study was 55 respondents. Meanwhile, the types and sources of data were obtained through primary data and secondary data. Data collection techniques were obtained from distributing questionnaires and interviews. Analysis of data obtained using quantitative analysis and business feasibility using R/C and BEP (Break Event Point) analysis. The results obtained in this research show that the feasibility of the palm sugar business in Marancar District, South Tapanuli Regency, North Sumatra Province is 1.261, which shows that every Rp. 1 spent will generate income of Rp. 1.26.